Vallecular Cholesterol Granuloma: Case Report - Vertelytė, Jūratė; Morozas, Arnoldas (Lietuvos chirurgija, 2023)
Introduction. Cholesterol granuloma is a rare benign cystic neoplasm characterised by a fibrous capsule, and a cystic fluid containing cholesterol crystals, multinucleated giant cells, erythrocytes and haemosiderin. Cholesterol granulomas are usually found in diverse parts of the temporal bone, most commonly – petrous apex. Very few cases of cholesterol granulomas in other organs have been reported, to our knowledge none are reported in the larynx. The main purpose of this case report is to highlight this extremely rare laryngeal lesion and its unique macroscopic appearance. Case report. A 55-year-old man is referred to the Ear, Nose and Throat Centre because of persistent hoarseness, globus sensation and complicated intubation due to a mass in the larynx. Videolaryngoscopy showed a large cyst-like mass in the vallecula, epiglottis was displaced towards the posterior pharyngeal wall and erythema of interarytenoid notch and arytenoid tubercle was present. A computerized tomography scan confirmed a cystic mass on the lingual surface of the epiglottis. On the basis of the examination and clinical symptoms, a diagnosis of chronic laryngitis, gastro-oesophageal reflux and an unspecified benign tumour of the respiratory system was made, surgical treatment was planned. The patient underwent microlaryngoscopy and surgical extirpation of the cyst using a CO2 laser, as the cyst was opened a yellowish, shiny, viscous fluid was observed. Two days later, laryngoscopy revealed fibrin plaque at the site of the cyst. Final diagnosis of cholesterol granuloma was formed based on histological examination of the mass. Conclusions. Cholesterol granulomas and masses in vallecula are extremly rare, but this case shows that cholesterol granuloma can be included in the differential diagnosis of cystic neoplasms of the larynx.